The Differences of Women’s Sexual Drive Condition between Triclofem and Cyclofem Users - Syabani, Sekar Arum Aisyah; Santoso, Budi; Annas, Jimmy Yanuar (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Various factors contribute to changes in the condition of a woman's sexual drive, one of which is the use of hormonal contraception. The majority of women of childbearing age use the injectable hormonal contraceptive method to prevent pregnancy. The injection method of contraception consists of two types, namely triclofem and cyclofem. However, until now it is not known with certainty the difference in sexual drive between triclofem and cyclofem contraception users. The purpose of this study was to compare the value of total sexual drive in users of triclofem and cyclofem contraception. Subjects and Method: A cross-sectional study was conducted in October 2022 at PMB Maria, Tambaksari District, Surabaya City. A total of 152 subjects were selected in this study. The dependent variable is sexual drive, the independent variable is the use of triclofem and cyclofem contraception. Data were analyzed using the Mann-Whitney test. Results: There was a significant difference between the mean sexual drive for users of triclofem contraception and the mean sexual drive for users of cyclofem contraception, namely users who were ?35 years old (p= 0.001), worked (p= 0.020), and had used contraception >2 years (p = 0.004). Contraceptive users aged <35 years (p=0.415), not working (0.082), and duration of contraceptive use ?2 years (p=0.578) showed no significant difference between the mean sexual drive of Triclofem contraceptive users and the mean sexual drive in users of cyclofem contraception. Conclusion: There was a significant difference between the condition of sexual drive in contraception users of triclofem and cyclofem only in users with characteristics of age ?35 years, working, and having used contraception for >2 years. Also, users of triclofem contraception show lower sexual drive than users of cyclofem contraception. Keywords: sexual drive, contraceptive users, triclofem, and cyclofem. Correspondence: Sekar Arum Aisyah Syabani. Midwifery Program Study, Faculty of Medicine, Universitas Airlangga, Indonesia. Jl. Mayjen Prof. Dr. Moestopo No.47, Pacar Kembang, Tambaksari, Surabaya 60132, East Java. Email: sekar.arum.aisyah-2019@fk.unair.ac.id. Mobile: +6281385876519.